Lymphoblastic leukemia following myelodysplastic syndromes or myelodysplastic/myeloproliferative neoplasms. Issue 12 (15th October 2019) - Xie, Wei; Chen, Zhining; Wang, Sa A.; Hu, Shimin; Li, Shaoying; Miranda, Roberto N.; Medeiros, L. Jeffrey; Tang, Guiling
Abstract: Lymphoblastic leukemia (ALL) following myelodysplastic syndrome (MDS) or myelodysplastic/myeloproliferative neoplasm (MDS/MPN) is very rare. We report five cases: four had ALL diagnosed after MDS or MDS/MPN and one had ALL and MDS diagnosed simultaneously. At the onset of ALL, all patients showed co-existing MDS or MDS/MPN. Map-back FISH was performed in four patients, showing that ALL and MDS were cytogenetically related in two patients and unrelated in the other two patients. All five patients were treated with ALL-based chemotherapies, two patients with ALL clonally related to MDS were refractory to the therapies, whereas the other three patients achieved remission. We conclude that ALL developed after MDS is extremely rare. In some patients, ALL is clonally related to MDS and these patients may be refractory to ALL-based chemotherapies. In other patients who have no evidence of clonal relation between ALL and MDS, these patients more likely respond to ALL-based treatment regimens.